Sustainable Development Goals (SDGs) Environmental Development Pillar: Underwater Nature Conservation in Sukarame Village, Pandeglang Regency - Chairinnisa, Keanya; Anggoma, Faries Fardian; Maolana, Anjar (Global Writing Academica Researching and Publishing, 2024)
The Sustainable Development Goals (SDGs), which are universally applicable, have become a primary focus across various sectors. One of the issues related to the SDGs is environmental concerns, including biodiversity programs such as Underwater Nature Conservation. The Underwater Nature Conservation program was implemented by PT Pertamina Patra Niaga Fuel Terminal Tanjung Gerem in Sukarame Village, Pandeglang Regency, West Java, Indonesia. This conservation program was driven by various factors, including natural and human-related ones. This study aimed to describe the procedures or methods in Coral Reef Conservation and examine the role of this conservation effort in contributing to the Village SGDs, specifically within the context of the Environmental Pillar. To achieve this objective, a qualitative descriptive approach with document analysis was conducted. The results indicate that the Coral Reef Conservation Program by PT Pertamina Patra Niaga Fuel Terminal Tanjung Gerem significantly contributes to the 14th aspect, namely the Marine Environment Awareness in the Environmental Pillar of Village SDGs. Additionally, coral reef conservation improves water quality, prevents contamination, protects coastlines and other infrastructure, ensures sustainable fisheries and other habitats, reduces marine debris, absorbs CO2, aids in climate change adaptation, and mitigates flooding and erosion. This effort also contributes to five other aspects of the Environmental Pillar of Village SDGs, including aspects 6, 11, 12, 13, and 15.